Congenital diaphragmatic defects that present late. Issue 11 (November 1989) - Malone, P S; Brain, A J; Kiely, E M; Spitz, L
Abstract : Twenty two patients (age range: 1 month to 11 years) were treated for congenital diaphragmatic defects (excluding hiatus hernia) in the six year period 1983-8. Presenting features were failure to thrive (n = 7), abdominal pain and vomiting (n = 4), chronic respiratory symptoms (n = 3), and inability to wean from ventilatory support (n = 3). The defect was an incidental finding in five patients. Operative repair was performed with no mortality or serious postoperative morbidity. Dramatic improvement occurred in 15 of the 17 symptomatic patients. Awareness of the differential diagnosis should avoid delay in diagnosis or inappropriate treatment. Surgical correction is strongly recommended in all cases.